2010
DOI: 10.1038/jp.2010.124
|View full text |Cite
|
Sign up to set email alerts
|

Length of life and treatment intensity in infants diagnosed prenatally or postnatally with congenital anomalies considered to be lethal

Abstract: Objectives: The objectives of this study were (1) to compare age at death and the intensity and cost of medical treatment for infants diagnosed prenatally or postnatally with congenital anomalies considered to be lethal.(2) To determine whether greater treatment intensity is associated with longer life.Study Design: This is a retrospective cohort study of all fetuses and neonates with congenital anomalies classified as lethal who were diagnosed or treated at the University of North Carolina Hospitals from Janu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
30
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 20 publications
2
30
0
Order By: Relevance
“…In addition, at the present time, there is very little literature on developmental outcomes [20,21]. This further impacts and reinforces the prevailing view that focuses on a limited quality of life and arguments against aggressive care [11][12][13]15]. There must be a move toward valuation of life and corresponding provision of treatment and examination of developmental gains rather than limited intervention or palliative care for infants with "lethal" or "severe" fetal abnormalities.…”
Section: Current Perspectivesmentioning
confidence: 97%
See 1 more Smart Citation
“…In addition, at the present time, there is very little literature on developmental outcomes [20,21]. This further impacts and reinforces the prevailing view that focuses on a limited quality of life and arguments against aggressive care [11][12][13]15]. There must be a move toward valuation of life and corresponding provision of treatment and examination of developmental gains rather than limited intervention or palliative care for infants with "lethal" or "severe" fetal abnormalities.…”
Section: Current Perspectivesmentioning
confidence: 97%
“…Writers in the areas of palliative care and bioethics largely recommend limited medical intervention or only the provision of comfort care for this population [12][13][14][15][16].…”
mentioning
confidence: 99%
“…He points to two recent case series where 25 to 44% of infants with Trisomy 13 and 18 survived for more than a year when treated aggressively, far above the 15% cutoff we employed in our definition. However, one of those series included only nine patients, 1 and the other consisted of neonates referred to a tertiary center for ongoing care after birth, indicating that their population was enriched for neonates who survived long enough to transfer. 2 Without data on the intensity of medical treatment and survival of the neonates who were not transferred, the unusually high survival rate at 1 year was likely due to selection bias rather than contemporary medical intervention.…”
Section: Reply To Mccaffreymentioning
confidence: 99%
“…Courtwright et al 1 report that the diagnosis of 'lethal' conditions prenatally leads to care that is less intense, lower cost and of similar survival benefit when compared with postnatally diagnosed cases. Based on these results, the authors conclude that 'highly aggressive interventions did not prolong survival in these cases and should not be offered.'…”
mentioning
confidence: 99%
“…Because aggressive treatment was not associated with prolonged survival, the authors concluded that it should not be offered. 7 This is a classic self-fulfilling prophecy. It is hard to know what the mortality rate would be with treatment if current outcome statistics are based on cohorts in which many affected infants die after termination of pregnancy and another large number of infants receive palliative care after birth.…”
Section: The Treatment Team Commentsmentioning
confidence: 99%